Fine-diameter microwave-absorbing SiC-based fiber. Issue 20 (20th February 2017) - Wang, Bowei; Li, Huimin; Xu, Limin; Chen, Jiangxi; He, Guomei
Abstract : An amorphous fine-diameter SiC fiber with excellent microwave-absorbing capacity at the X band was prepared from a new boron containing polytitanocarbosilane. Abstract : A fine-diameter silicon carbide (SiC) fiber is a promising reinforcing fiber for ceramic matrix composites with high temperature applications because of its high tensile strength and oxidation resistance. However, functional SiC fibers with microwave-absorbing properties are rarely reported. In this work, we report a new microwave-absorbing SiC-based fiber made from a new polymer containing titanium and boron (Si–C–Ti–B polymer) using a polymer precursor route. The evolution in morphology, microstructure and phase are studied by FT-IR, XRD, SEM, and TEM during the conversion of the polymer fiber into a ceramic fiber. The results show that the polymer fibers covert into inorganic fibers above 900 °C and maintain an amorphous state up to 1300 °C. The effect of pyrolysis-temperature (900–1300 °C) on the tensile strength, dielectric properties and microwave-absorption are also studied. The highest tensile strength of the obtained fiber is 1.2 GPa when produced at 1200 °C. The calculated reflection coefficient of the SiC-based fiber pyrolysed at 1200 °C with a thickness of 3.48 mm is less than −10 dB at the X band (8.2–12.4 GHz), which reveals that the obtained ceramic fiber has the potential to be a microwave-absorbing material. This study not only offers a new polymer precursor for new SiC-based fibers, but also provides a functional thermo-structural material.